Fertigation with nitrogen and humic substances on soil chemical attributes cultivated with west Indian cherry - Dias, Dayanne do Nascimento; Lima, Augusto Miguel N.; Cunha, Jailson Cavalcante; Cavalcante, Ítalo Herbert Lucena; Soares , Emanuelle Mercês Barros; Silva, Kátia Araújo da; Rodrigues, Marcos Sales; Silva, Talison Souza da (Comunicata Scientiae, 2023)
The use of humic substances (HS) in the soil can increase the efficiency of nitrogen fertilizers and contribute to the increment in soil organic matter and plant nutrient availability. Hence, this study aimed to evaluate, in two production cycles, the effect of applying HS and different nitrogen (N) doses on the chemical attributes and organic matter fractions of a soil cultivated with West Indian cherry in the Brazilian semiarid region. The experiment was set up in split plots, arranged in strips with four replicates. The absence or presence of HS using KS100 as the source was tested in the plots, and N fertilization (50; 75; 100; 125 and 150% of the recommended dose), using urea, was tested in the subplots. Soil pH, H+Al, Al3+, and Na+, K+, P, Ca2+, Mg2+, Fe2+, Mn2+ and Zn2+ contents were determined, and cation exchange capacity and bases saturation (V %) in the 0-0.2 and 0.2-0.4 m layers were calculated. Analyses of stocks of total organic carbon and carbon (C) of the humic acid, fulvic acid and humin fractions, and humic substances were performed. It was possible to observe that, in the second production cycle of West Indian cherry, the soils showed higher contents of nutrients available to plants. Increase in N availability did not enable a clear trend in the behavior of chemical attributes and organic C stocks in the soil. Under the studied conditions, KS100 application allowed a reduction in the C stocks of the HS of the soil.